(untitled) (Law, State and Telecommunications Review, 2021)
[Purpose] This text aims to present the factual and legal elemntes used by the Colombian Constitutional Court to issue Sentence T-030 0f 2020, in which the relationship between interner Access and education is made explicit. [Methodology] To prepare this analysis, it was decided to use a qualitative methodology with a critical-analytical approach referred to the sentence and the legal basis on which the protection of the right to education in favor of the rural child persone is decided. [Findings] The Constitutional Court estalisches that Access to the internet is a constitutional right that the State must provide in accordance with principle of progressivity that supports the quality of education, understood as an essential budget to access Sciences, knowledge and take an active part in public and social decisions that help a subject to become an actor of change and social interaction.